Modelagem e simulação dos músculos temporomandibulares - Garcia, Eduardo (Universidade do Vale do Rio dos Sinos, 2011)
Computer Graphics, Biomechanics, Temporomandibular Joint Medical simulators play an important role in the development of prototype prostheses, pre-surgical planning and better understanding of the mechanical phenomena involved in the muscles motor action. This thesis details modelling and simulation of the muscular system acting on the jaw. The model involves the use of three-dimensional bone models and muscle modelling based on Hill type actuators. Ligaments where modelled conerning their restrictions to mandible movement. This work was partially parameterized from real captured data in order to be used in medical applications. In addition, a new methodology is used in the simulation of muscles based on the concept of insertion curves, with many lines of action for each muscle group. A simulator was developed for real time model visualization, allowing individual muscle activation during simulation time. The trajectory described by the model was compared to the real captured data, remaining mostly within the the convex hull of the captured curves. Furthermore, the model described the desired border movements.
Keywords: Computação gráfica; Biomecânica; Articulação temporomandibular; Temporomandibular joint muscles; Modelling; Simulation; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação